TROIANE (LE) TROIANE (LE) (Rif. Codice opera principale : C6461) - Euripide; Cottafavi Vittorio; Euripide; Rubin De Cervin Ernesto (ROMA (ITALIA) RAI - RADIO TELEVISIONE ITALIANA / Distribuzione: UNIVIDEO)
TRAGEDIA GRECA. POSEIDONE. ATENA. ECUBA. CORIFEA. TALTIBIO. CASSANDRA. ANDROMACA MENELAO.
"Musica: Rubin De Cervin Ernesto; Sceneggiatura: Cottafavi Vittorio; "
"Lupi Roldano; Ruspoli Esmeralda; Ferrati Sarah; Angeleri Lia; Orlando Orazio; Guarnie"
PAL, STEREO
ITALIANO
Keywords: TRAGEDIA -- Codice MATERIA SPICS: 9961